Alveolar Lymphocyte Proliferation in Sarcoidosis Patients Induced by Propionibacterium acnes - Ohnoshi, Taisuke; Kobayashi, Yozo; Ejiri, Togo; Kishi, Toshiyuki; Nakata, Yasunari; Kimura, Ikuro; Fujita, Michio (Nihon Kyōbu Shikkan Gakkai zasshi, 1985)
In pulmonary sarcoidosis, interstitial mononuclear infiltrate consists of macrophages and lymphocytes as a characteristic, morphologic feature, and is recognized to represent the initial lesion. Considerable evidence has been reported that alveolar lymphocytes in pulmonary sarcoidosis are activated, but the activation mechanism is not known. The proliferation of lymphocytes, obtained by bronchoalveolar lavage in vitro incorporation of 3H-thymidine induced Propionibacterium acnes (P. acnes). The mean response rate of alveolar lymphocytes was 2.23±0.89 in nine untreated sarcoidosis patients, 0.85±0.17 in five sarcoidosis patients given prednisolone and 0.78±0.29 in 11 controls. It was significantly enhanced in untreated patients compared to both treated patients (p<0.01) and controls (p<0.001), but there was no significant difference in the response rates between treated patients and controls. The response rate of alveolar lymphocytes in four active patients with sarcoidosis (3.05±0.61) was significantly higher than that in four inactive patients (1.77±0.44) (p<0.05), and that in controls (p<0.001). In sarcoidosis patients, the response rates showed a good correlation with activities of serum lysozyme (r=0.695, p<0.01), and with percentages of lymphocyte in bronchoalveolar lavage fluids (r=0.591, p<0.05). There was a low correlation between angiotensin-converting enzyme activities and response rates (r=0.508, p0.1). The alveolar lymphocyte response rates induced by P. acnes reflect the disease activity of sarcoidosis. Neither peripheral lymphocytes in sarcoidosis patients nor in controls showed a response to P. acnes. It was suggested that alveolar lymphocytes in untreated patients with active sarcoidosis are sensitized with P. acnes, and that activated lymphocytes play a central role in the induction of alveolitis in sarcoidosis patients by P. acnes.